An assessment of the economywide effects on Vietnam's ongoing microeconomic reform - Le, Hoang Cuong (Curtin University, 2012)
Vietnam implemented the Doi Moi (or Renovation) policy in 1986. This policy involved the introduction of many structural reforms in an attempt to move Vietnam towards a market economy. As part of Doi Moi, Vietnam’s two ongoing microeconomic reform programs aimed at domestic enterprises are of particular significance, including state-owned enterprise (SOE) reforms and the private sector development (PSD) policy. This thesis develops a computable general equilibrium (CGE) model of Vietnam (referred to as VNGEM) with twenty four industries, six labour groups based on educational qualifications and one representative household, which aims to assess the likely effects of these reform programs on Vietnam’s national economic outcomes and industries.These reform programs are found to be pro-growth as reflected in their contribution to increasing aggregate output in both short and long run. This output increase is largely the result of export expansion and local market expansion due to relatively lower domestic price levels. Hence, Vietnam experiences an expansion in aggregate employment and a trade surplus in the short run. Likewise, these reform programs generate positive welfare effects on household consumption in the long run as real wages and labour incomes rise. In terms of industry winners and losers, the most favourably affected industries in the short run include steel, electrical, and textile, clothing and footwear (TCF), while the least favourably affected industries include construction and public administration. These least favourably affected industries are either non-traded or inward-oriented. Hence, they do not benefit much from trade expansion.Similarly, the most favourably affected industries in the long run include electrical, steel and other manufacturing, while the least favourably affected industries include rice and paddy, and oil, gas and petroleum (OGP). These industries are least favourably affected because of rising labour cost and an increasing land rental rate, which significantly hamper their economic activities.The findings in this thesis suggest that promoting the private sector and, at the same time, reducing or removing the preferential treatment by the government of the SOE sector can solve Vietnam’s employment problem. Export-oriented industries such as the TCF industry are well positioned to absorb Vietnam’s labour force. To reduce trade deficits, domestic import-substituting producers need to improve their product quality and prices that are comparable to foreign goods in the medium and long term. Besides providing vocational training for workers, the government need to improve domestic human capital through education, and research and development(R&D) in order to acquire a sufficient number of high-skilled personnel to work with new technologies, machinery and equipment. Finally, to achieve greater reform outcomes, SOE reforms should be extended to include medium to large SOEs across all industries.Some areas of improvement include: (i) managing and utilising the compensation funds more wisely; (ii) unleashing the private sector and encouraging its participation in the equitisation process; (iii) improving the fairness and transparency of the equitisation process; (iv) improving the asset valuation method and strictly governing activities related to management buyouts and bankruptcy; (v) establishing a new structure of corporate governance to provide checks and balances in an enterprise; and (vi) reducing the government’s political influence on SOEs and equitised SOEs.